A Longitudinal Analysis of the Impact of Child Custody Loss on Drug Use and Crime Among a Sample of African American Mothers - Harp, Kathi L. H. (2018)
This study examines the influence of child custody loss on drug use and crime among a sample of African American mothers. Two types of custody loss are examined: informal custody loss (child living apart from mother but courts not involved), and official loss (child removed from mother’s care by authorities). Methods—Using data from 339 African American women, longitudinal random coefficient models analyzed the effects of each type of custody loss on subsequent drug use and crime. Results—Results indicated that both informal and official custody loss predicted increased drug use, and informal loss predicted increased criminal involvement. Findings demonstrate that child custody loss has negative health implications for African American mothers, potentially reducing their likelihood of regaining or retaining custody of their children. Conclusions—This study highlights the need to integrate drug treatment and other types of assistance into family case plans to improve reunification rates and outcomes among mothers, children, and families. Additionally, the finding that informal loss predicts increased drug use suggests that community-based efforts within the mother’s social network could be implemented to intervene before child welfare system involvement becomes necessary